2012
DOI: 10.1051/0004-6361/201219399
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of the principal component analysis detection of polarized signatures using real stellar data

Abstract: The general context of this study is the post-processing of multiline spectropolarimetric observations of stars, and in particular the numerical analysis techniques aiming at detecting and characterizing polarized signatures. Using real observational data, we compare and clarify several points concerning various methods of analysis. We applied and compared the results of simple line addition, least-squares deconvolution, and denoising by principal component analysis to polarized stellar spectra available from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…One popular and very successful extraction technique which follows this line of arguments is the so called least-squares deconvolution (LSD, Donati et al 1997;Kochukhov et al 2010). Another method is the principal component analysis (PCA, Carroll et al 2007;Martínez González et al 2008;Carroll et al 2009;Paletou 2012) or the simple but very effective coherent addition of line profiles in the velocity or logarithmic wavelength domain (Semel et al 2009;Ramírez et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…One popular and very successful extraction technique which follows this line of arguments is the so called least-squares deconvolution (LSD, Donati et al 1997;Kochukhov et al 2010). Another method is the principal component analysis (PCA, Carroll et al 2007;Martínez González et al 2008;Carroll et al 2009;Paletou 2012) or the simple but very effective coherent addition of line profiles in the velocity or logarithmic wavelength domain (Semel et al 2009;Ramírez et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…This allows a very fast processing of the data. Another advantage is the denoising of the original data (see e.g., Bailer-Jones et al 1998or Paletou 2012in another con-A&A 573, A67 (2015 text though). The PCA also differs from the projection method Matisse, which uses specific projection vectors that are attached to each stellar parameter that is to be inverted (Recio-Blanco et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As compared to alternative methods such as χ 2 fitting to a library of (synthetic) spectra, as done by Munari et al (2005) for the analysis of the RAVE survey, for instance, the main advantages of PCA are in the reduction of dimensionality -a critical issue when dealing with high-resolution spectra also covering a very large bandwith -which allows a very fast processing of the data, and in the "denoising" of the original data (see e.g., Bailer-Jones et al 1998or Paletou 2012 in another context though). It also differs from another projection method such as Matisse which uses specific projection vectors attached, say, to each stellar parameter to be inverted (Recio-Blanco et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since PCA can represent the database in a scalar and vectoral manner, one can easily observe the direction change of the spectral lines in vectoral representation of the spectral database [24]. Paletou et al, 2012 showed that PCA is an efficient tool to extract Stokes parameters of the polarized stellar data [25]. Fig.…”
Section: B Pca Analysis Of L Shell Mo Synthetic Databasementioning
confidence: 99%